Can the influence of running performance in Olympic-distance triathlon be compensated for? - Fröhlich, M.; Balter, J.; Emrich, E.; Pieter, A. (Journal of Athletic Enhancement, 2014)
In Olympic-distance triathlon, the 10 km run is assumed to be decisive for winning. The performance in the 1.5 km swim and 40 km cycling plays only a subordinate role in winning. Simulation calculations based on the times achieved in each discipline were able to show that even above-average swimming and cycling times as well as training extensions in terms of training time by excellent swimmers and cyclists did not compensate for excellent running performance. Under the current conditions, only top running performance opens up any chance at succeeding at all.